Co-expression of aroma liberating enzymes in a wine yeast strain - De Klerk, Daniel (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc (Viticulture and Oenology. Institute for Wine Biotechnology))--University of Stellenbosch, 2009.